HETEROTOPIA IN TASTE: A STUDY OF RUKMINI SRINIVAS’S TIFFIN AND SHOBHA NARAYAN’S MONSOON DIARY - Babu, Jeremy Jain; George, Jinu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Rukmini Srinivas’s Tiffin Memories and Recipes of Indian Vegetarian Food and Shobha Narayan’s Monsoon Diary: A Memoir with Recipes are cookbook memoirs that present the author's close association with food while in their home country and abroad. Shobha Narayan and Rukmini Srinivas state that they have difficult encounters with food while visiting a foreign country. They recollect their taste memory from childhood, through their cookbook memoirs by incorporating their favourite recipes in them. The challenging scenario with food in the transnational space as an Indian diaspora in the United States of America has made them discuss it along with their own solutions. The transnational space of the immigrants in a foreign land can be observed as a heterotopia where the diaspora resides in a state of crisis, especially in association with the food that they consume due to the different cuisines to which they have to adapt.